PEMBELAJARAN MATEMATIKA DENGAN PETA KONSEP, ALAT PERAGA, DAN BELAJAR KELOMPOK - Saragih, Sahat (Jurnal Kependidikan, 2005)
Abstract The aim of this study was to improve interaction and learning achievement in mathematics through cooperative learning using concept maps and teaching aids. The research was a classroom action research conducted in 2 cycles. The class was one of the second year classes of the State Senior High School 11 Medan. In the first cycle, cooperative learning using concept maps and teaching aids was conducted. In the second cycle the cooperative learning was also conducted but by enforcing group discussions. Evaluation process was conducted by using self-reflection, group discussion, quizzes, and tests. The results showed that the cooperative learning approach using concept map and teaching aids could improve students’ interaction and achievement. Keywords: cooperative learning, concept map, teaching aids